2019
DOI: 10.1177/0300060519891290
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy suspected to be combined with Fabry disease or Alport syndrome: a case report

Abstract: Immunoglobulin A (IgA) nephropathy is the most common glomerular disease, and it often manifests as persistent microscopic hematuria or gross hematuria. Fabry disease and Alport syndrome are hereditary diseases caused by mutation of genes, and these diseases are rare in China. At present, patients can be diagnosed with IgA nephropathy by clinical manifestations and laboratory examinations, but there is still controversy about the simultaneous diagnosis of Alport syndrome and Fabry disease in patients with IgA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Having a family history of kidney disease with a diagnosis of IgA nephropathy, the patient was treated with the possibility of familial IgA nephropathy. However, the family was not thoroughly evaluated for Alport syndrome, while IgA nephropathy with Alport syndrome has been reported [ 3 ]. Alport Syndrome is a genetically heterogeneous disease caused by genes encoding alpha 3, 4, and 5 chains of IV collagen [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having a family history of kidney disease with a diagnosis of IgA nephropathy, the patient was treated with the possibility of familial IgA nephropathy. However, the family was not thoroughly evaluated for Alport syndrome, while IgA nephropathy with Alport syndrome has been reported [ 3 ]. Alport Syndrome is a genetically heterogeneous disease caused by genes encoding alpha 3, 4, and 5 chains of IV collagen [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…This patient had a family history of kidney disease with IgA nephropathy in family members, which led to a possible diagnosis of familial IgA nephropathy. Although family members were not thoroughly evaluated, such as electron-microscopic tissue examination and immunostaining for alpha-chain disorder and genetic studies, IgA nephropathy with Alport syndrome has been reported [ 3 ]. Another factor that led to the diagnosis of IgA nephropathy was the presence of familial IgA nephropathy with bilateral hearing impairment [ 13 ], although this is not common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One case report described a 9-mo-old boy who was diagnosed with concomitant ATS and Klinefelter syndrome, with a homozygous single-nucleotide substitution found in the splice site of intron 41 of the COL4A5 gene by genomic DNA analysis[ 7 ]. In addition, IgA nephropathy can accompany ATS[ 8 ]. A study in 2017 involved two boys with IgA nephropathy, whose pathogenic COL4A5 mutations were identified by polymerase chain reaction-based screening[ 9 ].…”
Section: Introductionmentioning
confidence: 99%